Optimizing printer usage through data analytics for enhanced institutional efficiency - Kadir, Fauwas Abdul; Sumanto, Sumanto (Institute of Computer Science (IOCS), 2025)
The advancement of information technology had simplified various workplace processes, including document processing and printing. In an institution, the use of printers played a crucial role in daily operations. However, without proper management, printer usage often became inefficient, leading to increased operational costs and unnecessary waste of resources. Therefore, an analytical system was needed to monitor and optimize printer usage. Such a system provided valuable insights by analyzing data generated from printing activities. This data analysis revealed patterns in work habits and allowed institutions to make informed decisions. As a result, institutions were able to improve operational efficiency, reduce costs, and minimize environmental impact. Paper and ink waste were significantly reduced by implementing data-driven policies. Overall, the integration of data analytics into printer management contributed to sustainable practices and better resource allocation in institutional environments.